COMPARATIVE STUDY: FORMULA PRAKTIS ESTIMASI LAJU FILTRASI GLOMERULUS(LFG) DENGAN BIOMARKER KREATININ SERUM - Irawan, Putra Adi; Farizal, Jon; Febrianto, Tedy (Politeknik Kesehatan Kemenkes Bengkulu, 2019)
Background: Estimation GFR is complicated to take a relatively long time, so it takes a practical and efficient method with accurate results as well. Indonesia is a country with moderately high chronic kidney disease patients. Riskesdas Data Ministry of Health 2013-2018 reported patients with kidney failure age ≥ 15 years of increasing each year. It takes several laboratory tests to give a proper picture of kidney health including: LFG. There are several formulas that have been researched earlier by experts including: Formula Chronic Kidney Disease-Epidemiology Collaboration (CKD-EPI), The isotope dilution mass spectrometry (ID-MS) Traceable Modification of Diet in Renal Disease (MDRD) , and Modification of Diet in Renal Disease (MDRD) 4 Variable. Objectives: Know the comparison of LFG estimates based on the formula CKD-EPI, ID-MS Traceable MDRD, and MDRD 4 Variable. Methods: Data used in research studies such as serum creatinine and subject age are obtained from secondary Data as much as 30 people. The GFR values are calculated with the CKD-EPI formula, ID-MS Traceable MDRD, and MDRD 4 Variable. Result: Average value of ± SD (n = 30) LFG based on the CKD-EPI formula is 71,36 ± 8.77 with the vulnerable value of GFR = 50,70-89,34. 93.30% suffered mild (60-89) and 6.70% Moderate damage (59-30). The average value of ± SD (n = 30) GFR based on the formula of the ID-MS Traceable MDRD is 64,79 ± 6,59 with vulnerable value of GFR = 48,48-78,40. 83.30% suffered mild (60-89) and 16.70% Moderate damage (59-30). Average value of ± SD (n = 30) GFR based on the MDRD 4 Variable formula is 68,86 ± 7,00 with vulnerable value GFR = 51,53-83,33. 93.30% suffered mild (60-89) and 6.70% Moderate damage (59-30). Conclusion: The use of three (3) such formulas can be used to estimate GFR. Nevertheless, the formula CKD-EPI or MDRD 4 variables are recommended.